Characterizations of contact CR-warped product submanifolds of nearly Sasakian manifolds - Ali, A.; Othman, W.A.M.; Ozel, C. (Balkan Society of Geometers, 2016)
In this paper, we study warped product contact CR-submanifolds of a nearly Sasakian manifold. We work out the characterizations in terms of tensor fields under which a contact CR-submanifold of a nearly Sasakian manifold reduces to a warped product submanifold.